Oasis: A computer vision approach to self watering system for green air purifier - Tan, Wei Jun (2025)
In this project, a blockchain-based e-commerce system is proposed to transform the online marketplace by addressing key challenges found in traditional e-commerce platforms. This project’s main objective is to eliminate middlemen or intermediaries to streamline transactions, reduce transaction costs, and enhance transparency and trust between buyers and sellers. By utilizing blockchain technology, the system provides decentralized transaction management, user identity verification, and product authenticity. This will provide a secure and efficient platform for e-commerce activities. On the other hand, the user interface is designed to be intuitive and user-friendly to facilitate seamless interaction with the smart contract functionalities. This system will not only redefine the e-commerce experience but also aligns with the sustainable practices by optimizing logistics and minimizing environmental impacts caused by ecommerce activities. This project aims to create an innovative e-commerce platform that is cost-effective, secure and environmentally responsible, which will enhance the user satisfaction and introducing a new era of digital commerce.